Acute administration of inorganic nitrate reduces VO2peak in endurance athletes - Bescos, R.; Rodriguez, F. A.; Iglesias, X.; Ferrer, M. D.; Iborra, E.; Pons, A. (Medicine & Science in Sports & Exercise, 2011)
Purpose: Humans can reduce inorganic nitrate (NO3-) to nitrite (NO2-), nitric oxide (NO), and other bioactive nitrogen oxides. The purpose of this study was to test the hypothesis that a single dose of inorganic nitrate before exercise might enhance the tolerance of endurance athletes to high intensity exercise.